A low-cost solid waste-based high-strength cementitious material and preparation method thereof
By mixing low-cost solid waste such as coal gangue, fly ash, desulfurization gypsum, slag, etc. with coupling enhancer and coated modified glass fiber, high-strength gelling materials are prepared, which solves the problem of insufficient strength of solid waste-based materials. It realizes efficient utilization of resources and environmental protection.
Patent Information
- Application Number
- CN202411472820.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-22
- Publication Date
- 2024-12-20
- Estimated Expiration
- 2044-10-22
AI Technical Summary
The existing solid waste-based gelling materials are insufficient in terms of strength, which is difficult to meet the needs of modern construction projects, and the accumulation of industrial solid waste and construction waste causes pollution to the environment.
By mixing coal gangue, fly ash, desulfurization gypsum, slag, silicate cement, bonding enhancer and coated modified glass fiber, low-cost solid waste-based high-strength gelling materials are prepared, and bonding enhancer and packaging are used. Mechanical properties and durability of over-modified glass fiber reinforced materials.
It significantly improves the mechanical properties and durability of gelled materials, reduces production costs, reduces environmental pressure, realizes efficient recycling of resources, and shows excellent toughness and crack resistance in fields such as construction.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention relates to the field of building materials, and in particular to a low-cost solid waste-based high-strength cementitious material and a preparation method thereof. Background Art
[0002] With the acceleration of urbanization and the continuous advancement of infrastructure construction, the demand for building materials is increasing. The production of traditional cementitious materials often relies on non-renewable resources, which is costly and puts a certain amount of pressure on the environment. At the same time, with the rapid development of industry, the increase of industrial solid waste is increasing day by day. The accumulation of a large amount of industrial solid waste and construction waste not only occupies land resources, but also causes serious pollution to the environment, seriously threatening the environment and ecological balance. Therefore, the use of low-cost solid waste to prepare cementitious materials has important practical significance for saving energy resources and improving environmental problems. However, the solid waste-based cementitious materials on the market are still insufficient in strength and it is difficult to meet the strength requirements of modern construction projects. Summary of the invention
[0003] In order to overcome the above-mentioned technical problems, the object of the present invention is to provide a low-cost solid waste-based high-strength cementitious material and a preparation method thereof. By evenly mixing coal gangue, fly ash, desulfurized gypsum, slag, silicate cement, a bonding enhancer and coated modified glass fiber, a low-cost solid waste-based high-strength cementitious material is obtained, which solves the problem that the existing solid waste-based cementitious materials have poor strength and are difficult to meet the strength requirements of modern construction projects.
[0004] The purpose of the present invention can be achieved through the following technical solutions:
[0005] A low-cost solid waste-based high-strength cementitious material, comprising the following components in parts by weight:
[0006] 55-65 parts of coal gangue, 16-22 parts of fly ash, 11-19 parts of desulfurized gypsum, 18-26 parts of slag, 33-46 parts of Portland cement, 1.5-7.7 parts of bonding enhancer and 1-10 parts of coated modified glass fiber;
[0007] Wherein, the bonding enhancer is prepared by the following steps:
[0008] Step a1: 2-chloro-5-nitrotrifluorotoluene, pentaerythritol, anhydrous potassium carbonate, toluene and N,N-dimethylformamide are added to a three-necked flask equipped with a stirrer, a thermometer and an air guide tube, and nitrogen is introduced for protection. The mixture is stirred for reaction at a temperature of 20-25° C. and a stirring rate of 300-400 r / min for 1-1.5 h, and then the temperature is raised to 135-140° C. and the stirring reaction is continued for 2-3 h, and then the temperature is raised to 150-155° C. and the stirring reaction is continued for 7-9 h. After the reaction is completed, the reaction product is cooled to room temperature, and then added to ice water, and then vacuum filtered. The filter cake is washed with distilled water and anhydrous methanol for 2-3 times in sequence, and then placed in a vacuum drying oven and dried at a temperature of 50-55° C. for 2-3 h to obtain intermediate 1;
[0009] Step a2: adding intermediate 1, reduced iron powder, acetone, ethanol, deionized water and concentrated hydrochloric acid to a three-necked flask equipped with a stirrer, a thermometer, an air guide tube and a reflux condenser, stirring and reacting for 25-30 minutes at a temperature of 20-25° C. and a stirring rate of 300-400 r / min, then heating to reflux and continuing to stir and react for 5-6 hours, then adjusting the pH to 8-9 with sodium hydroxide solution, then vacuum filtering while hot, pouring the filtrate into ice water to precipitate, then vacuum filtering, placing the filter cake in a vacuum drying oven, and drying it at a temperature of 50-55° C. for 2-3 hours to obtain intermediate 2;
[0010] Step a3: Add intermediate 2, isophorone diisocyanate, dibutyltin dilaurate and ethyl acetate to a three-necked flask equipped with a stirrer, a thermometer and an air duct, introduce nitrogen protection, stir the reaction at a temperature of 20-25°C and a stirring rate of 300-400r / min for 10-15min, then raise the temperature to 45-50°C and continue stirring the reaction for 8-10h. After the reaction is completed, the reaction product is cooled to room temperature, and then the solvent is removed by rotary evaporation to obtain a coupling enhancer.
[0011] As a further embodiment of the present invention: the usage ratio of the 2-chloro-5-nitrotrifluorotoluene, pentaerythritol, anhydrous potassium carbonate, toluene and N,N-dimethylformamide in step a1 is 42-45 mmol: 10 mmmol: 45-50 mmol: 20-25 mL: 50-60 mL.
[0012] As a further scheme of the present invention: the usage ratio of the intermediate 1, reduced iron powder, acetone, ethanol, deionized water and concentrated hydrochloric acid in step a2 is 10mmol:60-80mmol:20-30mL:20-30mL:20-30mL:20-30mL:8-10mL.
[0013] As a further solution of the present invention: the mass fraction of the concentrated hydrochloric acid in step a2 is 36-38%; the mass fraction of the sodium hydroxide solution is 20-25%.
[0014] As a further solution of the present invention: the usage ratio of the intermediate 2, isophorone diisocyanate, dibutyltin dilaurate and ethyl acetate in step a3 is 10 mmol: 40-45 mmol: 0.05-0.11 g: 80-100 mL.
[0015] As a further solution of the present invention: the coated modified glass fiber is prepared by the following steps:
[0016] Step b1: placing the glass fiber in a muffle furnace and calcining it at a temperature of 600-650° C. for 1-1.5 hours to obtain a surface-treated glass fiber;
[0017] Step b2: Add polysulfone and N,N-dimethylacetamide to a three-necked flask equipped with a stirrer and a thermometer, stir and react for 2-3 hours at a temperature of 20-25°C and a stirring rate of 300-400r / min, then add the surface-treated glass fiber and continue stirring and reacting for 1-2 hours at a temperature of 60-65°C. After the reaction, cool the reaction product to room temperature, then ultrasonically treat it for 30-40 minutes at an ultrasonic power of 200-250W, and then centrifuge it. Place the precipitate in a vacuum drying oven and dry it at a temperature of 40-45°C for 4-5 hours to obtain a coated modified glass fiber.
[0018] As a further solution of the present invention: the usage ratio of the polysulfone, N,N-dimethylacetamide and surface treated glass fiber in step b2 is 5-13 g: 100-110 mL: 5 g.
[0019] As a further solution of the present invention: the polysulfone in step b2 is PSF P3500.
[0020] As a further solution of the present invention: a method for preparing a low-cost solid waste-based high-strength cementitious material comprises the following steps:
[0021] Step 1: Weigh 55-65 parts of coal gangue, 16-22 parts of fly ash, 11-19 parts of desulfurized gypsum, 18-26 parts of slag, 33-46 parts of Portland cement, 1.5-7.7 parts of bonding enhancer and 1-10 parts of coated modified glass fiber according to weight, and set aside;
[0022] Step 2: Evenly mix coal gangue, fly ash, desulfurized gypsum, slag, silicate cement, bonding enhancer and coated modified glass fiber to obtain a low-cost solid waste-based high-strength cementitious material.
[0023] Beneficial effects of the present invention:
[0024] The invention discloses a low-cost solid waste-based high-strength cementitious material and a preparation method thereof. The low-cost solid waste-based high-strength cementitious material is obtained by uniformly mixing coal gangue, fly ash, desulfurized gypsum, slag, silicate cement, a bonding enhancer and coated modified glass fiber. The preparation method uses low-cost solid wastes such as coal gangue, fly ash, desulfurized gypsum and slag as main raw materials to prepare the cementitious material, realizes the comprehensive utilization of solid waste with high added value, greatly reduces the production cost, and greatly reduces the harm of solid waste storage to the environment. Then, a bonding enhancer and coated modified glass fiber are added to the cementitious material for strength. It can enhance the modification and significantly enhance the close bonding of the internal structure of the cementitious material, so that it can show excellent toughness and crack resistance when subjected to external forces. It not only gives the cementitious material a high degree of plasticity, mechanical strength, impact resistance and corrosion resistance, making it both strong and durable, thereby improving the comprehensive performance of the cementitious material. The cementitious material not only greatly reduces the dependence on high-value raw materials, reduces environmental pressure, and realizes the efficient recycling of resources, but also has great application potential in multiple engineering fields such as buildings, roads, and bridges, and effectively promotes the green development of infrastructure construction.
[0025] In the process of preparing the cementitious material, a bonding enhancer is first prepared. First, 2-chloro-5-nitrobenzotrifluoride and pentaerythritol are reacted. The chlorine atom on the 2-chloro-5-nitrobenzotrifluoride reacts with the hydroxyl group on the pentaerythritol to introduce a large number of nitro groups and trifluoromethyl groups to obtain intermediate 1. Then, intermediate 1 is reacted with reduced iron powder. The nitro group on intermediate 1 is reduced to amino group by the reduced iron powder to obtain intermediate 2. Finally, intermediate 2 is reacted with isophorone diisocyanate. The amino group on intermediate 2 reacts with an isocyanate group on isophorone diisocyanate. reaction, and at the same time, a large number of isocyanate groups are introduced to obtain a bonding enhancer; a large number of isocyanate groups in the molecular structure of the bonding enhancer can react with active groups (hydroxyl, amino, etc.) in other cementitious materials to form strong chemical bonds, thereby enhancing the bonding force between the components in the cementitious material and significantly improving the mechanical properties and durability of the material. At the same time, a large number of fluorine elements in the molecular structure of the bonding enhancer can reduce the surface energy of the cementitious material, enhance its hydrophobicity, and effectively resist the erosion of moisture, oxygen, and acidic and alkaline substances, thereby improving the weather resistance and chemical stability of the entire material.
[0026] In the process of preparing the gelling material, a coated modified glass fiber is also prepared. First, the glass fiber is calcined to remove impurities on its surface to obtain surface-treated glass fiber. Then, the surface-treated glass fiber is treated by dissolving polysulfone, and a coating layer is formed after drying to obtain coated modified glass fiber. Glass fiber is an inorganic non-metallic material with excellent performance, and has the advantages of high strength, high modulus, strong heat resistance, good corrosion resistance, good insulation, etc. After adding it to the gelling material, the glass fiber and the gelling material are intertwined and entangled to form a dense composite material structure. When the gelling material is subjected to external force, the glass fiber The fiber can span cracks or holes to form a bridging structure, thereby preventing the further expansion of the cracks, improving the overall strength and toughness of the material, and thus improving the material's ability to resist damage. Polysulfone has excellent corrosion resistance, heat resistance and mechanical strength. Coating polysulfone on the surface of glass fiber can form a dense protective layer, which can improve the shortcomings of glass fiber's brittleness and easy breakage, and can effectively isolate the glass fiber from the erosion of corrosive media, which not only enhances the corrosion resistance and durability of the glass fiber, but also enables it to better play its reinforcing role in the cementitious material and improve the mechanical properties of the overall material. DETAILED DESCRIPTION
[0027] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0028] Embodiment 1:
[0029] This embodiment is a method for preparing a low-cost solid waste-based high-strength cementitious material, comprising the following steps:
[0030] Step S1: 42mmol 2-chloro-5-nitrotrifluorotoluene, 10mmmol pentaerythritol, 45mmol anhydrous potassium carbonate, 20mL toluene and 50mL N,N-dimethylformamide were added to a three-necked flask equipped with a stirrer, a thermometer and an air guide tube, and nitrogen was introduced for protection. The mixture was stirred at 20°C and a stirring rate of 300r / min for 1h, and then the temperature was raised to 135°C and the stirring reaction was continued for 2h. The temperature was then raised to 150°C and the stirring reaction was continued for 7h. After the reaction was completed, the reaction product was cooled to room temperature, and then added to ice water, and then vacuum filtered. The filter cake was washed twice with distilled water and anhydrous methanol in sequence, and then placed in a vacuum drying oven and dried at 50°C for 2h to obtain intermediate 1;
[0031] Step S2: 10 mmol of intermediate 1, 60 mmol of reduced iron powder, 20 mL of acetone, 20 mL of ethanol, 20 mL of deionized water and 8 mL of 36% concentrated hydrochloric acid were added to a three-necked flask equipped with a stirrer, a thermometer, a gas guide tube and a reflux condenser, and stirred for reaction for 25 min at a temperature of 20° C. and a stirring rate of 300 r / min, and then the temperature was raised to reflux and the stirring reaction was continued for 5 h, and then the pH was adjusted to 8 with a 20% sodium hydroxide solution, and then vacuum filtered while hot, the filtrate was poured into ice water to precipitate, and then vacuum filtered, the filter cake was placed in a vacuum drying oven, and dried at a temperature of 50° C. for 2 h to obtain intermediate 2;
[0032] Step S3: 10 mmol of intermediate 2, 40 mmol of isophorone diisocyanate, 0.05 g of dibutyltin dilaurate and 80 mL of ethyl acetate were added to a three-necked flask equipped with a stirrer, a thermometer and a gas duct, and nitrogen was introduced for protection. The mixture was stirred at 20° C. and a stirring rate of 300 r / min for 10 min, and then the temperature was raised to 45° C. and the stirring reaction was continued for 8 h. After the reaction was completed, the reaction product was cooled to room temperature, and then the solvent was removed by rotary evaporation to obtain a coupling enhancer;
[0033] Step S4: placing the glass fiber in a muffle furnace and calcining it at 600° C. for 1 h to obtain a surface-treated glass fiber;
[0034] Step S5: Add 5 g of polysulfone PSF P3500 and 100 mL of N, N-dimethylacetamide to a three-necked flask equipped with a stirrer and a thermometer, stir and react for 2 h at a temperature of 20 ° C and a stirring rate of 300 r / min, then add 5 g of surface-treated glass fiber and continue stirring and reacting for 1 h under the condition of heating to 60 ° C. After the reaction, the reaction product is cooled to room temperature, and then ultrasonically treated for 30 min at an ultrasonic power of 200 W, and then centrifuged, and the precipitate is placed in a vacuum drying oven and dried at a temperature of 40 ° C for 4 h to obtain a coated modified glass fiber;
[0035] Step S6: weigh 55 parts of coal gangue, 16 parts of fly ash, 11 parts of desulfurized gypsum, 18 parts of slag, 33 parts of Portland cement, 1.5 parts of bonding enhancer and 1 part of coated modified glass fiber according to weight parts, and set aside;
[0036] Step S7: Evenly mix the coal gangue, fly ash, desulfurized gypsum, slag, silicate cement, bonding enhancer and coated modified glass fiber to obtain a low-cost solid waste-based high-strength cementitious material.
[0037] Embodiment 2:
[0038] This embodiment is a method for preparing a low-cost solid waste-based high-strength cementitious material, comprising the following steps:
[0039] Step S1: 44mmol 2-chloro-5-nitrotrifluorotoluene, 10mmmol pentaerythritol, 48mmol anhydrous potassium carbonate, 22mL toluene and 55mL N,N-dimethylformamide were added to a three-necked flask equipped with a stirrer, a thermometer and an air guide tube, and nitrogen was introduced for protection. The mixture was stirred at 22°C and a stirring rate of 350r / min for 1.2h, and then the temperature was raised to 138°C and the stirring reaction was continued for 2.5h. The temperature was then raised to 152°C and the stirring reaction was continued for 8h. After the reaction was completed, the reaction product was cooled to room temperature, and then added to ice water, and then vacuum filtered. The filter cake was washed twice with distilled water and anhydrous methanol in sequence, and then placed in a vacuum drying oven and dried at 52°C for 2.5h to obtain intermediate 1;
[0040] Step S2: 10 mmol of intermediate 1, 70 mmol of reduced iron powder, 25 mL of acetone, 25 mL of ethanol, 25 mL of deionized water and 9 mL of 37% concentrated hydrochloric acid were added to a three-necked flask equipped with a stirrer, a thermometer, a gas guide tube and a reflux condenser, and stirred for reaction for 28 min at a temperature of 22° C. and a stirring rate of 350 r / min, and then the temperature was raised to reflux and the stirring reaction was continued for 5.5 h, and then the pH was adjusted to 8.5 with a 22% sodium hydroxide solution, and then vacuum filtered while hot, the filtrate was poured into ice water to precipitate, and then vacuum filtered, the filter cake was placed in a vacuum drying oven, and dried at a temperature of 52° C. for 2.5 h to obtain intermediate 2;
[0041] Step S3: 10 mmol of intermediate 2, 42 mmol of isophorone diisocyanate, 0.08 g of dibutyltin dilaurate and 90 mL of ethyl acetate were added to a three-necked flask equipped with a stirrer, a thermometer and a gas duct, and nitrogen was introduced for protection. The mixture was stirred at 22° C. and a stirring rate of 350 r / min for 12 min, and then the temperature was raised to 48° C. and the stirring reaction was continued for 9 h. After the reaction was completed, the reaction product was cooled to room temperature, and then the solvent was removed by rotary evaporation to obtain a coupling enhancer;
[0042] Step S4: placing the glass fiber in a muffle furnace and calcining it at 625° C. for 1.2 h to obtain a surface-treated glass fiber;
[0043] Step S5: 9 g of polysulfone PSF P3500 and 105 mL of N,N-dimethylacetamide were added to a three-necked flask equipped with a stirrer and a thermometer, and the mixture was stirred at 22° C. and 350 r / min for 2.5 h. Then, 5 g of surface-treated glass fiber was added and the mixture was heated to 62° C. and stirred for 1.5 h. After the reaction, the reaction product was cooled to room temperature, and then ultrasonically treated for 35 min at an ultrasonic power of 225 W, and then centrifuged. The precipitate was placed in a vacuum drying oven and dried at 42° C. for 4.5 h to obtain a coated modified glass fiber.
[0044] Step S6: weigh 60 parts of coal gangue, 19 parts of fly ash, 15 parts of desulfurized gypsum, 22 parts of slag, 40 parts of Portland cement, 4.6 parts of bonding enhancer and 5.5 parts of coated modified glass fiber according to weight parts, and set aside;
[0045] Step S7: Evenly mix the coal gangue, fly ash, desulfurized gypsum, slag, silicate cement, bonding enhancer and coated modified glass fiber to obtain a low-cost solid waste-based high-strength cementitious material.
[0046] Embodiment 3:
[0047] This embodiment is a method for preparing a low-cost solid waste-based high-strength cementitious material, comprising the following steps:
[0048] Step S1: 45mmol 2-chloro-5-nitrotrifluorotoluene, 10mmmol pentaerythritol, 50mmol anhydrous potassium carbonate, 25mL toluene and 60mL N,N-dimethylformamide were added to a three-necked flask equipped with a stirrer, a thermometer and an air guide tube, and nitrogen was introduced for protection. The mixture was stirred for reaction at 25°C and a stirring rate of 400r / min for 1.5h, and then the mixture was heated to 140°C and continued to stir for reaction for 3h, and then the mixture was heated to 155°C and continued to stir for reaction for 9h. After the reaction, the reaction product was cooled to room temperature, and then added to ice water, and then vacuum filtered. The filter cake was washed three times with distilled water and anhydrous methanol in sequence, and then placed in a vacuum drying oven and dried at 55°C for 3h to obtain intermediate 1;
[0049] Step S2: 10 mmol of intermediate 1, 80 mmol of reduced iron powder, 30 mL of acetone, 30 mL of ethanol, 30 mL of deionized water and 10 mL of 38% concentrated hydrochloric acid were added to a three-necked flask equipped with a stirrer, a thermometer, a gas guide tube and a reflux condenser, and stirred for reaction at a temperature of 25° C. and a stirring rate of 400 r / min for 30 min, then heated to reflux and continued to stir for 6 h, then adjusted the pH to 9 with a 25% sodium hydroxide solution, then vacuum filtered while hot, poured the filtrate into ice water to precipitate, then vacuum filtered, placed the filter cake in a vacuum drying oven, and dried at a temperature of 55° C. for 3 h to obtain intermediate 2;
[0050] Step S3: 10 mmol of intermediate 2, 45 mmol of isophorone diisocyanate, 0.11 g of dibutyltin dilaurate and 100 mL of ethyl acetate were added to a three-necked flask equipped with a stirrer, a thermometer and a gas duct, and nitrogen was introduced for protection. The mixture was stirred at 25° C. and a stirring rate of 400 r / min for 15 min, and then the temperature was raised to 50° C. and the stirring reaction was continued for 10 h. After the reaction was completed, the reaction product was cooled to room temperature, and then the solvent was removed by rotary evaporation to obtain a coupling enhancer;
[0051] Step S4: placing the glass fiber in a muffle furnace and calcining it at 650° C. for 1.5 h to obtain a surface-treated glass fiber;
[0052] Step S5: 13 g of polysulfone PSF P3500 and 110 mL of N, N-dimethylacetamide were added to a three-necked flask equipped with a stirrer and a thermometer, and the mixture was stirred for reaction at a temperature of 25° C. and a stirring rate of 400 r / min for 3 h, and then 5 g of surface-treated glass fiber was added and the mixture was heated to 65° C. and stirred for reaction for 2 h. After the reaction, the reaction product was cooled to room temperature, and then ultrasonically treated for 40 min at an ultrasonic power of 250 W, and then centrifuged. The precipitate was placed in a vacuum drying oven and dried at a temperature of 45° C. for 5 h to obtain a coated modified glass fiber;
[0053] Step S6: weigh 65 parts of coal gangue, 22 parts of fly ash, 19 parts of desulfurized gypsum, 26 parts of slag, 46 parts of Portland cement, 7.7 parts of bonding enhancer and 10 parts of coated modified glass fiber according to weight parts, and set aside;
[0054] Step S7: Evenly mix the coal gangue, fly ash, desulfurized gypsum, slag, silicate cement, bonding enhancer and coated modified glass fiber to obtain a low-cost solid waste-based high-strength cementitious material.
[0055] Comparative Example 1:
[0056] This comparative example is a method for preparing a low-cost solid waste-based high-strength cementitious material, comprising the following steps:
[0057] Step S1: weigh 65 parts of coal gangue, 22 parts of fly ash, 19 parts of desulfurized gypsum, 26 parts of slag and 46 parts of Portland cement according to weight parts and set aside;
[0058] Step S2: Evenly mix coal gangue, fly ash, desulfurized gypsum, slag and silicate cement to obtain a low-cost solid waste-based high-strength cementitious material.
[0059] Comparative Example 2:
[0060] This comparative example is a method for preparing a low-cost solid waste-based high-strength cementitious material, comprising the following steps:
[0061] Step S1: 45mmol 2-chloro-5-nitrotrifluorotoluene, 10mmmol pentaerythritol, 50mmol anhydrous potassium carbonate, 25mL toluene and 60mL N,N-dimethylformamide were added to a three-necked flask equipped with a stirrer, a thermometer and an air guide tube, and nitrogen was introduced for protection. The mixture was stirred for reaction at 25°C and a stirring rate of 400r / min for 1.5h, and then the mixture was heated to 140°C and continued to stir for reaction for 3h, and then the mixture was heated to 155°C and continued to stir for reaction for 9h. After the reaction, the reaction product was cooled to room temperature, and then added to ice water, and then vacuum filtered. The filter cake was washed three times with distilled water and anhydrous methanol in sequence, and then placed in a vacuum drying oven and dried at 55°C for 3h to obtain intermediate 1;
[0062] Step S2: 10 mmol of intermediate 1, 80 mmol of reduced iron powder, 30 mL of acetone, 30 mL of ethanol, 30 mL of deionized water and 10 mL of 38% concentrated hydrochloric acid were added to a three-necked flask equipped with a stirrer, a thermometer, a gas guide tube and a reflux condenser, and stirred for reaction at a temperature of 25° C. and a stirring rate of 400 r / min for 30 min, then heated to reflux and continued to stir for 6 h, then adjusted the pH to 9 with a 25% sodium hydroxide solution, then vacuum filtered while hot, poured the filtrate into ice water to precipitate, then vacuum filtered, placed the filter cake in a vacuum drying oven, and dried at a temperature of 55° C. for 3 h to obtain intermediate 2;
[0063] Step S3: 10 mmol of intermediate 2, 45 mmol of isophorone diisocyanate, 0.11 g of dibutyltin dilaurate and 100 mL of ethyl acetate were added to a three-necked flask equipped with a stirrer, a thermometer and a gas duct, and nitrogen was introduced for protection. The mixture was stirred at 25° C. and a stirring rate of 400 r / min for 15 min, and then the temperature was raised to 50° C. and the stirring reaction was continued for 10 h. After the reaction was completed, the reaction product was cooled to room temperature, and then the solvent was removed by rotary evaporation to obtain a coupling enhancer;
[0064] Step S4: weigh 65 parts of coal gangue, 22 parts of fly ash, 19 parts of desulfurized gypsum, 26 parts of slag, 46 parts of Portland cement and 7.7 parts of bonding enhancer according to weight parts, and set aside;
[0065] Step S5: Evenly mix the coal gangue, fly ash, desulfurized gypsum, slag, silicate cement and bonding enhancer to obtain a low-cost solid waste-based high-strength cementitious material.
[0066] Comparative Example 3:
[0067] This comparative example is a method for preparing a low-cost solid waste-based high-strength cementitious material, comprising the following steps:
[0068] Step S1: placing the glass fiber in a muffle furnace and calcining it at 650° C. for 1.5 h to obtain a surface-treated glass fiber;
[0069] Step S2: 13 g of polysulfone PSF P3500 and 110 mL of N, N-dimethylacetamide were added to a three-necked flask equipped with a stirrer and a thermometer, and the mixture was stirred for reaction at a temperature of 25° C. and a stirring rate of 400 r / min for 3 h, and then 5 g of surface-treated glass fiber was added and the mixture was heated to 65° C. and stirred for reaction for 2 h. After the reaction, the reaction product was cooled to room temperature, and then ultrasonically treated for 40 min at an ultrasonic power of 250 W, and then centrifuged. The precipitate was placed in a vacuum drying oven and dried at a temperature of 45° C. for 5 h to obtain a coated modified glass fiber;
[0070] Step S3: weigh 65 parts of coal gangue, 22 parts of fly ash, 19 parts of desulfurized gypsum, 26 parts of slag, 46 parts of Portland cement and 10 parts of coated modified glass fiber according to weight parts, and set aside;
[0071] Step S4: Evenly mix the coal gangue, fly ash, desulfurized gypsum, slag, silicate cement and coated modified glass fiber to obtain a low-cost solid waste-based high-strength cementitious material.
[0072] 30% of the weight of water was added to the low-cost solid waste-based high-strength cementitious materials of Examples 1-3 and Comparative Examples 1-3, and the mixture was stirred evenly to form a slurry, which was then poured into a mortar test mold, vibrated and allowed to stand, demolded after 24 hours, and placed in a standard curing room for natural curing at a temperature of 20°C and a relative humidity of 95%. The test blocks were tested, and the test results are shown in the following table:
[0073]
[0074] Referring to the data in the above table, based on the comparison between Examples 1-3 and Comparative Examples 1-3, it can be seen that adding a bonding enhancer and coating modified glass fiber can significantly improve the mechanical strength of low-cost solid waste-based high-strength cementitious materials, and the synergistic effect of the two can achieve the best improvement effect.
[0075] In the description of this specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.
[0076] The above contents are merely examples and explanations of the present invention. Those skilled in the art may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the invention or exceed the scope defined by the claims, they shall all fall within the protection scope of the present invention.
Claims
1. A low-cost solid waste-based high-strength cementitious material, characterized in that: It comprises the following components in parts by weight: 55-65 parts of coal gangue, 16-22 parts of fly ash, 11-19 parts of desulfurized gypsum, 18-26 parts of slag, 33-46 parts of Portland cement, 1.5-7.7 parts of bonding enhancer and 1-10 parts of coated modified glass fiber; Wherein, the bonding enhancer is prepared by the following steps: Step a1: 2-chloro-5-nitrotrifluorotoluene, pentaerythritol, anhydrous potassium carbonate, toluene and N,N-dimethylformamide are added to a three-necked flask equipped with a stirrer, a thermometer and an air guide tube, and nitrogen is introduced for protection. The mixture is stirred for reaction at a temperature of 20-25° C. and a stirring rate of 300-400 r / min for 1-1.5 h, and then the temperature is raised to 135-140° C. and the stirring reaction is continued for 2-3 h, and then the temperature is raised to 150-155° C. and the stirring reaction is continued for 7-9 h. After the reaction is completed, the reaction product is cooled to room temperature, and then added to ice water, and then vacuum filtered. The filter cake is washed with distilled water and anhydrous methanol for 2-3 times in sequence, and then placed in a vacuum drying oven and dried at a temperature of 50-55° C. for 2-3 h to obtain intermediate 1; Step a2: adding intermediate 1, reduced iron powder, acetone, ethanol, deionized water and concentrated hydrochloric acid to a three-necked flask equipped with a stirrer, a thermometer, an air guide tube and a reflux condenser, stirring and reacting for 25-30 minutes at a temperature of 20-25° C. and a stirring rate of 300-400 r / min, then heating to reflux and continuing to stir and react for 5-6 hours, then adjusting the pH to 8-9 with sodium hydroxide solution, then vacuum filtering while hot, pouring the filtrate into ice water to precipitate, then vacuum filtering, placing the filter cake in a vacuum drying oven, and drying it at a temperature of 50-55° C. for 2-3 hours to obtain intermediate 2; Step a3: Add intermediate 2, isophorone diisocyanate, dibutyltin dilaurate and ethyl acetate to a three-necked flask equipped with a stirrer, a thermometer and an air guide tube, introduce nitrogen protection, stir and react for 10-15 minutes at a temperature of 20-25° C. and a stirring rate of 300-400 r / min, then heat to 45-50° C. and continue stirring and reacting for 8-10 hours. After the reaction is completed, cool the reaction product to room temperature, and then remove the solvent by rotary evaporation to obtain a coupling enhancer; The coated modified glass fiber is prepared by the following steps: Step b1: placing the glass fiber in a muffle furnace and calcining it at a temperature of 600-650° C. for 1-1.5 hours to obtain a surface-treated glass fiber; Step b2: Add polysulfone and N,N-dimethylacetamide to a three-necked flask equipped with a stirrer and a thermometer, stir and react for 2-3 hours at a temperature of 20-25°C and a stirring rate of 300-400r / min, then add the surface-treated glass fiber and continue stirring and reacting for 1-2 hours at a temperature of 60-65°C. After the reaction, cool the reaction product to room temperature, then ultrasonically treat it for 30-40 minutes at an ultrasonic power of 200-250W, and then centrifuge it. Place the precipitate in a vacuum drying oven and dry it at a temperature of 40-45°C for 4-5 hours to obtain a coated modified glass fiber.
2. A low-cost solid waste-based high-strength cementitious material according to claim 1, characterized in that: The usage ratio of the 2-chloro-5-nitrotrifluorotoluene, pentaerythritol, anhydrous potassium carbonate, toluene and N,N-dimethylformamide in step a1 is 42-45 mmol: 10 mmmol: 45-50 mmol: 20-25 mL: 50-60 mL.
3. The low-cost solid waste-based high-strength cementitious material according to claim 1, characterized in that: The usage ratio of the intermediate 1, reduced iron powder, acetone, ethanol, deionized water and concentrated hydrochloric acid in step a2 is 10 mmol: 60-80 mmol: 20-30 mL: 20-30 mL: 20-30 mL: 8-10 mL.
4. The low-cost solid waste-based high-strength cementitious material according to claim 1, characterized in that: The mass fraction of the concentrated hydrochloric acid in step a2 is 36-38%; the mass fraction of the sodium hydroxide solution is 20-25%.
5. The low-cost solid waste-based high-strength cementitious material according to claim 1, characterized in that: The usage ratio of the intermediate 2, isophorone diisocyanate, dibutyltin dilaurate and ethyl acetate in step a3 is 10 mmol: 40-45 mmol: 0.05-0.11 g: 80-100 mL.
6. The low-cost solid waste-based high-strength cementitious material according to claim 1, characterized in that: The usage ratio of the polysulfone, N,N-dimethylacetamide and surface treated glass fiber in step b2 is 5-13 g: 100-110 mL: 5 g.
7. A method for preparing a low-cost solid waste-based high-strength cementitious material according to any one of claims 1 to 6, characterized in that: The following steps are involved: Step 1: Weigh 55-65 parts of coal gangue, 16-22 parts of fly ash, 11-19 parts of desulfurized gypsum, 18-26 parts of slag, 33-46 parts of Portland cement, 1.5-7.7 parts of bonding enhancer and 1-10 parts of coated modified glass fiber according to weight, and set aside; Step 2: Evenly mix coal gangue, fly ash, desulfurized gypsum, slag, silicate cement, bonding enhancer and coated modified glass fiber to obtain a low-cost solid waste-based high-strength cementitious material.
